First record of Triplax russica (Linnaeus, 1758) (Coleoptera, Erotylidae) from Kazakhstan - Izbasar I. Temreshev (Acta Biologica Sibirica, 2023)
Pleasing fungus beetle Triplax russica (Linnaeus, 1758) from the family Erotylidae is firstly recorded from Kazakhstan. A key to known species of the genus Triplax from Kazakhstan is given. Birch brittlegill Russula betularum Hora, stinking russula Russula foetens Pers., 1796, are recorded from Kazakhstan for T. russica.